(untitled) (Estudios humanísticos. Geografía, historia y arte, 2021)
About the middle of the l3th century, El Bierzo was the scenary of a serious social conflict, led by the town hall of Ponferrada, that rose up «in arms» against the king’s «merino» and the monks of Carracedo, when the latter wanted to have under their authority the men from the enclosure of S. Andrés de Montejos who had become «inhabitants» of Ponferrada. This conflict, that comes to an end with the triumph of the monastery, does not have to be considered as a fight town hall aristocracy, but rather, as a confrontation within the upper classes monastery urban oligarchy that show some similar interests in the appropriation of the income from the other social classes.